INDEPENDENCE AND EDUCATION. REFLEXIONS UPON THE BICENTENARY - Laviña, Javier (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
This article presents a vision of the education after the revolt of the Pasquines (Posters) that appeared in the city of Santa Fe of Bogota in 1794. In this article we analyze proposal offered in the colonial authorities to face the problems that affected, between other areas, that of the education. To avoid the social conflict, it proposes to finish with the studies of the New Philosophy, to close the printers and the Library. Likewise, the propose to intervene in the catechism of the catholic doctrine to introduce questions and answers that reinforce the paper of the crown and the loyalty of the subjects.